2021
DOI: 10.1007/s42690-021-00504-9
|View full text |Cite
|
Sign up to set email alerts
|

Fruit fly surveillance in Togo (West Africa): state of diversity and prevalence of species

Abstract: The production and marketing of fruits, especially mango, in sub-Saharan Africa are threatened by fruit flies (Diptera: Tephritidae). This baseline study analysed the biodiversity of fruit fly species, in mango orchards, in different ecological zones of Togo. Traps used to monitor the flies in the orchards consisted of dry baits, made from four types of parapheromones specific to the males of different species. Forty species of fruit flies were identified in the mango orchards in Togo. The most common species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The frequent encounter of Z. cucurbitae, D. punctatifrons and D. bivittatus across the ecological zones as dominant agricultural pests have been also reported in different parts of Africa [2,15,28,42,49]. The other species from the genus Dacus were also found but in low numbers, often represented by very few specimens per field.…”
Section: Diversity Of Fruit Fliesmentioning
confidence: 79%
See 2 more Smart Citations
“…The frequent encounter of Z. cucurbitae, D. punctatifrons and D. bivittatus across the ecological zones as dominant agricultural pests have been also reported in different parts of Africa [2,15,28,42,49]. The other species from the genus Dacus were also found but in low numbers, often represented by very few specimens per field.…”
Section: Diversity Of Fruit Fliesmentioning
confidence: 79%
“…The SSA alone harbours more than 1,000 species of fruit flies, of which 29 are considered of major economic significance to fruit and vegetable crops [53,62]. The vast majority of these are indigenous to SSA while a few are of exotic origin [2,35,46]. The impacts of fruit fly infestation on horticultural crops in SSA continue to be a major challenge to farmers [2,35,46], and the biodiversity monitoring studies have been few and have contributed to the further development of management strategies [ 2,29,30,42,48,54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha diversity responds to change in seasonal distribution of a resource (mango postharvest stage), agroclimatic factors at the study site (Martínez et al 2023), and dominance of a pest species over a host (Isabirye et al 2015) as reported for Tephritidae (Amevoin et al 2021). Dissimilarity in beta diversity of fruit flies was mostly explained by nesting and less spatial rotation of species, suggesting establishment of species in the study area, overlap between them, and competition between A. ludens and A. obliqua on the same host (mango).…”
Section: Discussionmentioning
confidence: 99%
“…In West Africa, fruit fly species of economic importance belong to genera Bactrocera, Ceratitis, Dacus and Zeugodacus (De Meyer et al, 2013Vayssières et al, 2007Vayssières et al, , 2014Zida et al, 2020). Among these species, Dacus ciliates Loew and Zeugodacus cucurbitae (Coquillett) associated with Cucurbitaceae; Ceratitis capitata (Wiedemann) associated with citrus; Ceratitis cosyra (Walker) and Bactrocera dorsalis (Hendel) associated with citrus, cashew, shea, guava and especially mango are the most economically important in this region (Vayssières et al, 2014;Zida et al, 2020;Amevoin et al, 2021;Mutamiswa et al, 2021). Furthermore, B. dorsalis, an invasive species, native to Asia and identified for the first time in Africa in 2003, and currently found in all West African countries, is the major pest associated with fruit production (De Meyer et al, 2010;Vayssières et al, 2014).…”
Section: Introductionmentioning
confidence: 99%